Recurrent vaginal discharge causing by retained foetal bones in a bitch: a case report - G. Serin; U. Parin (Veterinární Medicína, 2009)
An 18-month-year old mixed breed bitch was referred to the Animal Hospital of Adnan Menderes University suffering from recurrent serous vaginal discharge for two months. Her temperature, pulsation, appetite and also hematologic parameters were normal. Transabdominal ultrasound scan revealed fullness in bifurcation uteri and bright echoes suggestive of bone caudally. During hysterotomy, retained foetal bones were observed in corpus uteri but not removed as they had become embedded in the uterine wall. Therapy of this case was completed with ovariohysterectomy operation. No aerobic bacteria were isolated from both samples taken from the vaginal discharge and retained foetal bones in the uterine cavity. Although rare, veterinary clinicians should be aware of this problem also in young bitches with no general symptoms and are well advised to use genital ultrasonography in examinations.